2020
DOI: 10.1111/jfbc.13325
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect ofCapsicum annumagainst ethanol‐induced oxidative stress and renal apoptosis

Abstract: The present study explored the ameliorative potency of aqueous extract of Capsicum annum (AqCA), against oxidative imbalance and renal toxicity induced by ethanol. Randomly grouped male Wistar rats (n = 6), were marked as ethanol-treated (2 g/kg bw, i.p.), CA 125 (125 mg/kg bw, i.p.), CA 250 (250 mg/kg bw, i.p.), ethanol pre-treated with CA (similar doses), and control (0.5 ml normal saline, i.p.), and treated for 30 consecutive days. Biochemical analysis of tissue and serum parameters was performed, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…For example, pepper exhibited antioxidant activity in reducing ethanol‐induced oxidative stress in the cells of the gastric and intestinal mucosa by increasing the activities of antioxidant enzymes, such as SOD, glutathione S‐transferase, glutathione reductase, and CAT (Prakash & Srinivasan, 2010). Similarly, Wistar rats treated with aqueous extracts of C. annuum prior to alcohol treatment showed a protective effect against renal toxicity and alcohol‐induced oxidative stress, indicating its protective effect against nephrotoxicity induced by routine alcohol consumption (Das et al., 2021). The study observed decreased oxidative stress, inflammation, and apoptosis following treatment with the pepper extracts, which was evident from reduced alterations in the serum and tissue properties compared to alcohol treatment.…”
Section: Health‐promoting Effects Of Pepper Antioxidantsmentioning
confidence: 99%
“…For example, pepper exhibited antioxidant activity in reducing ethanol‐induced oxidative stress in the cells of the gastric and intestinal mucosa by increasing the activities of antioxidant enzymes, such as SOD, glutathione S‐transferase, glutathione reductase, and CAT (Prakash & Srinivasan, 2010). Similarly, Wistar rats treated with aqueous extracts of C. annuum prior to alcohol treatment showed a protective effect against renal toxicity and alcohol‐induced oxidative stress, indicating its protective effect against nephrotoxicity induced by routine alcohol consumption (Das et al., 2021). The study observed decreased oxidative stress, inflammation, and apoptosis following treatment with the pepper extracts, which was evident from reduced alterations in the serum and tissue properties compared to alcohol treatment.…”
Section: Health‐promoting Effects Of Pepper Antioxidantsmentioning
confidence: 99%
“…Herbal protectors may prevent damage of normal tissues selectively. The biological effects is thus reduced and repair begins [14].…”
Section: Introductionmentioning
confidence: 99%